Supply Chain DigitalModel for Educational Management in the Credit Bank System - Artaphon Chansamut (International Journal of Supply Chain Management, 2023)
The paper about supply chain digital model for educational management in the credit bank system. The objectives of this research: research were to study supply chain digital model for educational management in the credit bank system and to access the efficiency development of the model .The sample groups were ten experts in supply chain. Data analysis was the average mean and standard deviation. The research was found that supply chain digital model for educational management in the credit bank system consists of seven components: namely main components, Suppliers, Manufacturer, graduated Students, Customers, Satisfaction and Feedback The results from experts agreement about supply chain digital model for educational management in the credit bank system was a high level. It showed that supply chain digital model for educational management in the credit bank system could be used to support the tasks.